The Relationship Between Employee Motivation, Creativity and Performance - Z, Nurhaeda; Maryadi, Maryadi; Salim, M; Kitta, Syafruddin (Fakultas Ekonomi, Universitas Muslim Indonesia, 2024)
This research explores the relationship between employee motivation, creativity, and performance, focusing on the interaction between intrinsic and extrinsic motivations and the role of organizational strategies, leadership support, and resource availability in enhancing motivation and creativity. Using a qualitative case study approach, the study involves semi-structured interviews, focus groups, and document analysis with employees and leaders from a mid-sized technology company. Thematic analysis was employed to identify key themes related to motivation, creativity, and performance. The findings reveal that intrinsic motivation significantly enhances creative productivity, while extrinsic rewards complement intrinsic motivation when aligned with employees' values. Transformational leadership and a supportive organizational culture are crucial in fostering an environment conducive to creativity. Adequate resources and well-designed workspaces that encourage collaboration further boost motivation and creativity. Training programs focused on creative problem-solving and developing a growth mindset also play a vital role. This study provides valuable insights for managers and policymakers on creating environments that foster innovation and sustain high levels of employee engagement. Organizations can enhance creativity and performance by understanding the interplay between different motivational factors and the importance of supportive leadership and resources. Future research should consider mixed-method approaches and diverse organizational contexts to validate and expand upon these findings.